Mechanical and In Vitro Biological Performance of Graphene Nanoplatelets Reinforced Calcium Silicate Composite - Mehrali, Mehdi (Public Library of Science, 2014)
Calcium silicate (CaSiO(3), CS) ceramic composites reinforced with graphene nanoplatelets (GNP) were prepared using hot isostatic pressing (HIP) at 1150°C. Quantitative microstructural analysis suggests that GNP play a role in grain size and is responsible for the improved densification. Raman spectroscopy and scanning electron microscopy showed that GNP survived the harsh processing conditions of the selected HIP processing parameters. The uniform distribution of 1 wt.% GNP in the CS matrix, high densification and fine CS grain size help to improve the fracture toughness by ∼130%, hardness by ∼30% and brittleness index by ∼40% as compared to the CS matrix without GNP. The toughening mechanisms, such as crack bridging, pull-out, branching and deflection induced by GNP are observed and discussed. The GNP/CS composites exhibit good apatite-forming ability in the simulated body fluid (SBF). Our results indicate that the addition of GNP decreased pH value in SBF. Effect of addition of GNP on early adhesion and proliferation of human osteoblast cells (hFOB) was measured in vitro. The GNP/CS composites showed good biocompatibility and promoted cell viability and cell proliferation. The results indicated that the cell viability and proliferation are affected by time and concentration of GNP in the CS matrix.